The Technological Basis of a Balloon-Expandable TAVR System: Non-occlusive Deployment, Anchorage in the Absence of Calcification and Polymer Leaflets - Appa, Harish; Park, Kenneth; Bezuidenhout, Deon; van Breda, Braden; de Jongh, Bruce; de Villiers, Jandré; Chacko, Reno; Scherman, Jacques; Ofoegbu, Chima; Swanevelder, Justiaan; Cousins, Michael; Human, Paul; et al. (Frontiers in Cardiovascular Medicine, 2022)
Leaflet durability and costs restrict contemporary trans-catheter aortic valve replacements (TAVR) largely to elderly patients in affluent countries. TAVR that are easily deployable, avoid secondary procedures and are also suitable for younger patients and non-calcific aortic regurgitation (AR) would significantly expand their global reach. Recognizing the reduced need for post-implantation pacemakers in balloon expandable (BE) TAVR and the recent advances with potentially superior leaflet materials, a trans-catheter BE-system was developed that allows tactile, non-occlusive deployment without rapid pacing, direct attachment of both bioprosthetic and polymer leaflets onto a shape-stabilized scallop and anchorage achieved by plastic deformation even in the absence of calcification. Three sizes were developed from nickel-cobalt-chromium MP35N alloy tubes: Small/ 23mm, Medium/ 26mm and Large/ 29mm. Crimp-diameters of valves with both bioprosthetic (sandwich-crosslinked decellularized pericardium) and polymer leaflets (triblock polyurethane combining siloxane and carbonate segments) matched those of modern clinically used BE TAVR. Balloon expansion favored the wing-structures of the stent thereby creating supra-annular anchors that exceeded the outer diameter at the waist level by 26.5±0.4% to 29.5±0.6%. In the pulse duplicator, polymer and bioprosthetic TAVR showed equivalent fluid dynamics with excellent EOA, pressure gradients and regurgitation volumes. Post-deployment fatigue resistance surpassed ISO requirements. The radial force of the helical deployment balloon at different filling pressures resulted in a fully developed anchorage profile of the valves from two thirds of their maximum deployment diameter onwards. By combining a unique balloon-expandable TAVR system that also caters for non-calcific AR with polymer leaflets, a powerful, potentially disruptive technology for heart valve disease has been incorporated into a TAVR that addresses global needs. While fulfilling key prerequisites for expanding the scope of TAVR to the vast number of patients of low- to middle income countries living with rheumatic heart disease the system may eventually also bring hope to the patients of high-income countries presently excluded from TAVR for being too young.